1990
DOI: 10.1159/000146994
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorus Content of Lysosomes in Hepatocytes and Kupffer Cells

Abstract: In the present study, the distribution of phosphorus was analyzed within lysosomes of hepatocytes, Kupffer cells and mast cells in untreated liver tissue of mice by the use of electron-spectroscopic imaging, a new electron-microscopical method which combines microanalysis with ultrastructural representation and allows to image the spatial distribution of light elements such as· N or P in cells and tissues. The obtained analytical data unfolded marked differences regarding the phosphorus content of lysosomes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Maybe the ultracentrifugation of Ars 200cHG and the resulting changes in its microparticle composition can be related to this result, since the biggest particles present before centrifugation could also be phagocytosed, stimulating the cells. [38][39][40][41] The correlation between electric current flow through the liquids and the type of the vial used corroborates the hypothesis in which metal particles in suspension could improve conductivity 1,2,21,41 and possible organic contaminants from plastic could impair it. The size of these particles seems not to be important in this case, since Ars 200cHGC (only the supernatant of the medicine, after ultra-centrifugation) presented the highest values of electric current flow.…”
Section: Discussionsupporting
confidence: 71%
“…Maybe the ultracentrifugation of Ars 200cHG and the resulting changes in its microparticle composition can be related to this result, since the biggest particles present before centrifugation could also be phagocytosed, stimulating the cells. [38][39][40][41] The correlation between electric current flow through the liquids and the type of the vial used corroborates the hypothesis in which metal particles in suspension could improve conductivity 1,2,21,41 and possible organic contaminants from plastic could impair it. The size of these particles seems not to be important in this case, since Ars 200cHGC (only the supernatant of the medicine, after ultra-centrifugation) presented the highest values of electric current flow.…”
Section: Discussionsupporting
confidence: 71%
“…edge, appear as bright dots in micrographs taken at energy losses beyond the P L2,? edge, a difference which seems to be far more pronounced than reported for GTA-fixed and Araldite-embedded hepatocytes (Kopf-Maier, 1990). In addition, heterochromatin regions exhibit a considerable increase in signal intensity when comparing micrographs taken at AE = 110-1 15 eV and AE = 150-155 eV.…”
Section: Discussionmentioning
confidence: 69%
“…Köpf-Maier investigated the phosphorus content of lysosomes in hepatocytes and Kupffer cells and found that the lysosomes of Kupffer cells always comprise phosphorus in high density, whereas the hepatocyte lysosomes did not. Köpf-Maier concluded that the elemental composition of lysosomes in hepatocytes and Kupffer cells exhibited a pronounced and unexpected heterogeneity …”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Kopf-Maier concluded that the elemental composition of lysosomes in hepatocytes and Kupffer cells exhibited a pronounced and unexpected heterogeneity. 34 Tapper and Sundler assessed how different agents affecting intracellular pH influenced the secretion of lysosomal β-N-acetyl hexosaminidase and preloaded fluorescein-labeled dextran from cultured mouse PMs. Nigericin raised the lysosomal pH in both K + -and Na + -based media.…”
Section: ■ Introductionmentioning
confidence: 99%